2023
DOI: 10.1259/bjr.20230058
|View full text |Cite
|
Sign up to set email alerts
|

Image guidance and interfractional anatomical variation in paediatric abdominal radiotherapy

Abstract: Objectives: To identify variables predicting inter fractional anatomical variationsmeasured with cone-beam CT (CBCT) throughout abdominal paediatric radiotherapy, and to assess the potential of surface-guided radiotherapy (SGRT) to monitor these changes. Methods: Metrics of variation in gastrointestinal (GI) gas volume andseparation of the body contour and abdominal wallwere calculated from 21 planning CTs and 77 weekly CBCTs for 21 abdominal neuroblastoma patients (median 4y, range: 2 –19y). Age, sex, feeding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
(43 reference statements)
0
2
0
Order By: Relevance
“…However, a recent study showed that SGRT may also be able to detect gastrointestinal variations triggering adaptive RT pathways. 21 For deep-seated target volumes, especially those moving independently of bony anatomy, other imaging techniques using CBCT or MRI are generally more accurate for localization. 6 However, SGRT can reduce target localization uncertainty due to intrafraction motion by the real-time monitoring of the patient surface.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a recent study showed that SGRT may also be able to detect gastrointestinal variations triggering adaptive RT pathways. 21 For deep-seated target volumes, especially those moving independently of bony anatomy, other imaging techniques using CBCT or MRI are generally more accurate for localization. 6 However, SGRT can reduce target localization uncertainty due to intrafraction motion by the real-time monitoring of the patient surface.…”
Section: Discussionmentioning
confidence: 99%
“…Taylor et al investigated the potential role of SGRT for the management of interfractional gastrointestinal gas volume variation in paediatric abdominal RT. 21 The key idea is that while SGRT would not replace cone beam CT (CBCT) imaging, it could enable a fully personalized Image Guided Radiotherapy (IGRT) schedule for each patient and reduce CBCT imaging to only required fractions. Also, SGRT systems have been recommended as a safety feature in paediatric treatments to assist in patient set-up and provide additional error detection.…”
Section: Introductionmentioning
confidence: 99%